Studi Karakteristik Evaluasi Volumetrik Marshall Campuran AC-BC Studi Kasus Material Agregat di Lawawoi Kab. Sidrap - Muharraran Muharraran; Rahmawati Rahmawati; Hendro Widarto; Adnan Adnan; Hamka Hamka (Pusat Riset dan Inovasi Nasional, 2024)
The condition of existing pavement layers in Sidenreng Rappang Regency is generally damaged before reaching the planned age. This study aims to evaluate volumetric marshall on aggregate performance in pavement mixtures and physical properties of aggregates. Experimental methods at the Road and Asphalt Laboratory of Muhammadiyah University of Parepare based on 2018 Bina Marga general specifications. The results of the research with volumetric marshall analysis the maximum stability value of 5.5% was 1469.78 kg and the minimum 4.5% was 1175.82 kg. The maximum VMA value of 6.5% was 16.21% and the minimum 4.5% was 14.25%. The maximum VIM value of 4.5% was 5.54% and the minimum of 6.5% was 3.13%. The maximum VFB value of 6.5% was 80.73% and the minimum of 4.5% was 61.13%. The maximum flow value of 5.5% was 3.67 mm and the minimum of 6% was 3.41 mm. The maximum marshall quotient value of 5.5% was 413.64 kg/mm and the minimum of 4.5% was 323.80 kg/mm. In stability, flow, marshall quotient and VMA have met the 2018 Bina Marga General specifications at asphalt levels of 4.5%, 5.0%, 5, 5%, 6%, and 6.5%. While the VIM and VFA values do not meet the specifications at 4.5% asphalt content. This shows that material quality affects the physical properties of aggregates in the performance of pavement mixtures.